Veränderungen in der Farmwirtschaft Südafrikas/Namibias zwischen 1965 und 1980 - Bähr, Jürgen (ERDKUNDE, 1981)
A comparison between the author’s own questionning and mapping in the period 1965/66 and again in 1979/80 is made use of in an attempt to answer the three questions which follow: 1. To what degree has the development of farms been continued over the past one and a half decades, and what was the effect of the political uncertainties of the recent past? 2. Has the transition to regulated rotational grazing led to a change in the composition, number and quality of livestock? 3. What sort of shifts in the structure of farm sizes can be observed,and in how far are they related to the development of farms? The results can be summarised as follows: 1. Remarkable progress has been made during the last 15 years in the development of farms in the entire farming zone of South West Africa; controlled rotational grazing was introduced almost everywhere. Economic, and in part political, reasons, however, continue to prevent development measures which are dependent upon an increase in the recruitment of labour. 2. Changes in grazing techniques have influenced stocking densities and the composition of animal stocks only in a few cases, whereas the quality of products was considerably enhanced. 3. The development of the structure of farm sizes is characterized by an increase in the number of large farms and smaller enterprises, together with a reduction in the number of medium-sized farms. It was not possible to establish a regular relationship between farm development and the structure of farm size.